Sociodemographic and clinical characteristics of suspected difficult-to-treat depression - Murao, Masami; Matsumoto, Yasuyuki; Kurihara, Mariko; Oe, Yuki; Nagashima, Izumi; Hayasaka, Tomonari; Tsuboi, Takashi; Watanabe, Koichiro; Sakurai, Hitoshi (Frontiers in Psychiatry, 2024)
Introduction: Difficult-to-treat depression (DTD) represents a broad spectrum of patients with persistent depression where standard treatment modalities are insufficient, yet specific characteristics of this group remain insufficiently understood. This investigation aims to delineate the sociodemographic and clinical profiles of suspected DTD patients in real-world clinical settings. Method: We conducted a retrospective analysis of data from patients comprehensively evaluated for suspected DTD at Kyorin University Hospital, Tokyo, Japan, between October 2014 and September 2018. The study participants consisted of individuals with persistent depression unresponsive to conventional antidepressant treatments during the current episode. Diagnoses adhered to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision. Additional evaluations included the Montgomery-Åsberg Depression Rating Scale (MADRS) and other pertinent measures. The analysis focused on comparing demographic and clinical characteristics across diagnosed groups. Results: The analysis encompassed 122 patients, with diagnoses of major depressive disorder (MDD) in 41.8%, bipolar disorder (BD) in 28.7%, and subthreshold depression in 29.5%. Notably, high incidences of psychiatric comorbidities were present across all groups, with anxiety disorders exceeding 30% and personality disorders surpassing 50%. The only significant distinction among the three groups was observed in the MADRS scores, with the MDD group exhibiting the highest values (20.9±9.7 vs. 18.6±9.3 vs. 11.3±7.4, p<0.01). Conclusions: This study sheds light on the intricate nature of suspected DTD, emphasizing the coexistence of MDD, BD, and subthreshold depression within this category. Our findings underscore the necessity for thorough evaluations and tailored treatment approaches for managing suspected DTD.